The Cambridge introduction to eighteenth-century poetry - Sitter, John E. (Cambridge introductions to literature., 2011)
"For readers daunted by the formal structures and rhetorical sophistication of eighteenth-century English poetry, this introduction by John Sitter brings the techniques and the major poets of the period 1700-1785 triumphantly to life. Sitter begins by offering a guide to poetic forms ranging from heroic couplets to blank verse, then demonstrates how skilfully male and female poets of the period used them as vehicles for imaginative experience, feelings and ideas. He then provides detailed analyses of individual works by poets from Finch, Swift and Pope, to Gray, Cowper and Barbauld. An approachable introduction to English poetry and major poets of the eighteenth century, this book provides a grounding in poetic analysis useful to students and general readers of literature"--